Diversity and Population of Non-Parasitic Nematodes in Various Accessions of Pepper (Piper nigrum L.) Bangka Island - Lesta, Lesta; Ningsih, Riski Meliya; Badriyah, Badriyah; Felisha, Nita Anggi (Program Studi Agroteknologi Universitas Siliwangi, 2025)
Nematodes are soil organisms that play an essential role in agricultural ecosystems, both as plant pathogens and soil health indicators. Non-parasitic nematodes or free-living nematodes play an essential role in soil food webs. This study aims to analyze the diversity and population of non-parasitic nematodes in Piper nigrum L. from various pepper accessions on Bangka Island. soil samples taken from seven locations and extracting nematodes using centrifugation flotation techniques. Nematodes were identified based on morphological characteristics by using a stereo and binocular microscopes and validated to the nematode identification keybook. The population of identified nematodes was calculated using the absolute population calculation formula. The results showed variations of non-parasitic nematodes in each location, which were influenced by environmental factors and types of pepper accessions. The most dominant population of identified nematodes was classified as Rhabditidae with 92.42%, Mononchidae, and Aphelenchus avenae (92.42%). The nematode population in Lampung Daun Lebar accession was 41 individuals, Lampung Daun Kecil (17), Nyelungkup (9), and Merapin (healthy control) 65 individuals. Non-parasitic nematodes have roles as bacterivores (soil bacteria eaters), fungivores (soil fungus eaters), predators of parasitic nematodes, and decomposers in the soil.